2011
DOI: 10.1177/1352458511426737
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cataract and glaucoma in patients with multiple sclerosis

Abstract: Background: The aim of the study was to evaluate whether multiple sclerosis (MS) is associated with risk of cataract or glaucoma. Methods:We conducted a population-based cohort study utilizing the UK General Practice Research Database (1987Database ( -2009 linked to the national hospital registry of England (1997England ( -2008. Incident MS patients (5576 cases) were identified and each was matched to six patients without MS (controls) by age, gender, and practice. Cox proportional hazard models were used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
(71 reference statements)
0
18
0
Order By: Relevance
“…The incidence of cataracts and glaucoma was not increased in the MS population overall as compared to age, sex and regionally matched controls. 49 However, the risk of cataracts (HR 2.45; 95% CI: 1.56–3.86) and glaucoma (HR 1.70; 95% CI: 1.01–2.86) were increased in individuals under age 50 years, that is individuals who were relatively young to develop these conditions. The prevalence of vision problems was nearly five-fold higher in the MS population than matched controls in one case-control study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of cataracts and glaucoma was not increased in the MS population overall as compared to age, sex and regionally matched controls. 49 However, the risk of cataracts (HR 2.45; 95% CI: 1.56–3.86) and glaucoma (HR 1.70; 95% CI: 1.01–2.86) were increased in individuals under age 50 years, that is individuals who were relatively young to develop these conditions. The prevalence of vision problems was nearly five-fold higher in the MS population than matched controls in one case-control study.…”
Section: Resultsmentioning
confidence: 99%
“…Based on one well-designed study, the risk of cataracts and glaucoma was increased in younger individuals (<50 years old). 49 This may reflect improved ascertainment due to more frequent ophthalmologic care. This study found that two commonly used therapies, anticonvulsants and corticosteroids were associated with increased risks of cataracts, while corticosteroid use was also associated with an increased risk of glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…The study cohort consisted of all patients aged ≥18 years old who had at least one diagnosis of MS in either GPRD or HES between January 1, 2001 and March 31, 2008 (last date at which data for GPRD, HES, and death certificates were still available) [10,11]. Use of validated MS criteria could not be used in these data sources, as these are only sparsely completed.…”
Section: Methodsmentioning
confidence: 99%
“…The cohort was necessarily larger than the linked cohorts, with more patients diagnosed in primary care (49%) and longer follow-up, presenting a lower mortality rate. The all data cohort explored eligibility further by including all patients and incorporating linked data where it was available; resembling the patient set and analyses reported in some previous publications [ 15 , 16 , 17 ]. This cohort primarily included patients from primary care (71%), and included longer follow-up, presenting a mortality rate 20% lower than the linked exposure and outcome cohort.…”
Section: Discussionmentioning
confidence: 99%